1980
DOI: 10.1055/s-0038-1650054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neutral Proteases from Human Leukocytes on Structure and Biological Properties of Human Factor VIII

Abstract: SummaryHuman factor VIII was purified from cryoprecipitate and incubated for up to 24 hours with four neutral proteases of human blood leukocytes, namely, with elastase-like protease (ELP), chymotrypsin-like protease (CLP), collagenase and gelatinase. Electrophoretic patterns showed a reproducible sequence of degradation of factor VIII and of its 230,000 molecular weight subunit by ELP and CLP. Intermediate products were similar but those resulting from exhaustive proteolysis by ELP and CLP differed distinctly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…However, because the patients with a normal platelet count after the initiation of chemotherapy had almost normal multimeric composition, the enzymatic modification of vWf by protease(s) released from platelets or the selective consumption of large multimers in high platelet count states may be responsible for the vWf abnormalities. Recent studies have indicated that platelet calcium-activated protease and neutral proteases of polymorphonuclear leucocytes can degrade the vWf molecule in vitro (Kopec et al 1980;Kunicki, Montgomery & Shulleck 1985;Thompson & Howard 1986). More recently, it has been shown that vWf fragmentation occurs due to in-vivo proteolysis in the patients with CMPD (Budde et al 1986;Lopez-Fernandez et al 1987), and that abnormal vWf structure was not corrected even if blood was obtained in the presence of protease inhibitors (Lopez-Fernandez et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…However, because the patients with a normal platelet count after the initiation of chemotherapy had almost normal multimeric composition, the enzymatic modification of vWf by protease(s) released from platelets or the selective consumption of large multimers in high platelet count states may be responsible for the vWf abnormalities. Recent studies have indicated that platelet calcium-activated protease and neutral proteases of polymorphonuclear leucocytes can degrade the vWf molecule in vitro (Kopec et al 1980;Kunicki, Montgomery & Shulleck 1985;Thompson & Howard 1986). More recently, it has been shown that vWf fragmentation occurs due to in-vivo proteolysis in the patients with CMPD (Budde et al 1986;Lopez-Fernandez et al 1987), and that abnormal vWf structure was not corrected even if blood was obtained in the presence of protease inhibitors (Lopez-Fernandez et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil elastase is a protease produced in the lisosome and is released in response to inflammation. Neutrophil elastase exhibits proteolytic activity on connective tissues, 2 blood coagulation, fibrinolytic factors 3 and complement factors 4 . It is believed that ARDS‐related lung injury is triggered by these actions of NE.…”
Section: Introductionmentioning
confidence: 99%
“…PMNE is reported to inhibit the activity of or to degrade fibrin [15], fibrinogen [16], platelets [17], AT [18,19], and coagulation factors [8,20]. Therefore, inhibition of the activity of the PMNE by ulinastatin [1,2] would induce coagulation and fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were drawn through an arterial catheter in the radial artery. The plasma concentration of PMNE was measured as the concentration of PMNE-α 1 -antitrypsin complex, with an enzyme-linked immunosorbent assay (ELISA), using antibody for α 1 -antitrypsin (Kitasato Biochemical Laboratory, Sagamihara, Kanagawa, Japan) [8]. AT was measured by a chromogenic peptide substrate method (COBAS; Roche, Tegimenta, Switzerland).…”
Section: Introductionmentioning
confidence: 99%